Besedni red in členki - Smolej, Mojca (Jezik in slovstvo, 2025)
Particles are a loosely defined set of lexemes as a part of speech, which is also understandable. Scientific works that address particles differ primarily at the level of defining functional or semantic-syntactic roles. In addition to their functional “elusiveness”, their word order characteristics are also partially unexplored, as well as the relationships between individual particles and parts of speech with which particles can stand. The starting condition for studying the word order rules of any particle, especially emphatic ones, is the knowledge of the particle‘s distributional constraints. Particles, whether modal or emphatic, cannot “freely roam” within a sentence. Based on the word order analysis of selected particles, we can extract six fundamental rules. The first rule concerns recognizing the basic function or meaning of the particle. The word order and meaning/function of the particle are often necessarily interconnected. The second rule refers to the structural and phonetic conditioning (emphasis) of word order realization. The third rule is related to the possibility of neglecting certain emphasizing particles (e.g. also, even, especially). The positioning of a particle is often conditioned by the ellipsis of the predicate. The fourth rule pertains to the necessity of considering all word formation laws. The fifth rule indicates that it is essential to include possible regional constants in the analysis of word order laws. The final rule is related to modal particles, which strengthen or weaken certainty inclination. Within this rule, there are several specifics. One of them manifests itself in the shifting of the modal particle towards the rheme, when the modal function of strengthening or weakening certainty inclination approaches the role of emphasizing particles, which only enter into a relationship with the particle directly preceding them.
Keywords: besedni red; cohesion; členki; distribucija; distribution; modification; modifikacija; particles; povezovanje; word order